2015
DOI: 10.1111/icad.12120
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Coleoptera and other invertebrates in urban gardens: a case study in a New Zealand city

Abstract: 1. Invertebrate biodiversity was investigated in 55 domestic gardens in the city of Dunedin in southern New Zealand. The influence of habitat types within the gardens (lawns, open beds, and closed canopy beds) on invertebrate community structure was investigated by pitfall trapping. Species richness of Coleoptera, the proportion of native species, and effects of pesticide use by householders was examined.2. The most abundantly trapped taxa were Collembola, Amphipoda, and Diptera. Most taxa were represented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
(52 reference statements)
2
11
0
Order By: Relevance
“…Kuschel's (1990) landmark study showed that native trees and bush patches in urban Auckland support far more diverse endemic beetle communities than exotic vegetation. While research has shown that urban gardens and some types of exotic vegetation in New Zealand can support diverse invertebrate assemblages (Barratt et al, 2015;Harris, Toft, Dugdale, Williams, & Rees, 2004) and some native bird species (Waite et al, 2013), the fauna that exotic vegetation supports tend to be exotic species, or native generalist species with flexible foraging strategies (Gardner-Gee, Stanley, & Beggs, 2015;Kuschel, 1990;Müller, Ignatieva, Nilon, Werner, & Zipperer, 2013;van Heezik, Smyth, & Mathieu, 2008;Waite et al, 2013). A study of bird use of urban vegetation in Hamilton (New Zealand) found that many native birds, including the insectivorous grey warbler (Gerygone igata) and fantail (Rhipidura fuliginosa), were most abundant in gardens with higher native plant biomass (Day, 1995), while Dunedin greenbelt fragments with higher proportions of native plants contain more native birds, and fewer exotic birds, than fragments dominated by exotic vegetation (van Heezik et al, 2008).…”
Section: 2mentioning
confidence: 99%
“…Kuschel's (1990) landmark study showed that native trees and bush patches in urban Auckland support far more diverse endemic beetle communities than exotic vegetation. While research has shown that urban gardens and some types of exotic vegetation in New Zealand can support diverse invertebrate assemblages (Barratt et al, 2015;Harris, Toft, Dugdale, Williams, & Rees, 2004) and some native bird species (Waite et al, 2013), the fauna that exotic vegetation supports tend to be exotic species, or native generalist species with flexible foraging strategies (Gardner-Gee, Stanley, & Beggs, 2015;Kuschel, 1990;Müller, Ignatieva, Nilon, Werner, & Zipperer, 2013;van Heezik, Smyth, & Mathieu, 2008;Waite et al, 2013). A study of bird use of urban vegetation in Hamilton (New Zealand) found that many native birds, including the insectivorous grey warbler (Gerygone igata) and fantail (Rhipidura fuliginosa), were most abundant in gardens with higher native plant biomass (Day, 1995), while Dunedin greenbelt fragments with higher proportions of native plants contain more native birds, and fewer exotic birds, than fragments dominated by exotic vegetation (van Heezik et al, 2008).…”
Section: 2mentioning
confidence: 99%
“…Kuschel (1990) found during a 15-year survey of urban gardens in Auckland the presence of 81 novel foreign species of beetles and weevils (Coleoptera spp.). These findings suggest that monitoring domestic gardens can be valuable in biosecurity surveillance, not only near ports of possible entry of new species but also because they are repositories for new plants distributed by nurseries (Barratt et al, 2015). Barratt et al (2015) also found that their study stimulated considerable interest from participants, which suggests that with appropriate engagement householders can effectively participate in biosecurity surveillance.…”
Section: Community Gardens and Biosecurity Riskmentioning
confidence: 81%
“…Research in New Zealand also has demonstrated the value of monitoring domestic gardens to detect incursions of new insect species (Barratt et al, 2015;Kotze et al, 2011). Barratt et al (2015) also found that their study stimulated considerable interest from participants, which suggests that with appropriate engagement householders can effectively participate in biosecurity surveillance. These findings suggest that monitoring domestic gardens can be valuable in biosecurity surveillance, not only near ports of possible entry of new species but also because they are repositories for new plants distributed by nurseries (Barratt et al, 2015).…”
Section: Community Gardens and Biosecurity Riskmentioning
confidence: 95%
See 2 more Smart Citations